Functional interactions of DNA topoisomerases with a human replication origin - Abdurashidova, Gulnara (Nature Publishing Group, 2007)
The human DNA replication origin, located in the lamin B2 gene, interacts with the DNA topoisomerases I and II in a cell cycle-modulated manner. The topoisomerases interact in vivo and in vitro with precise bonds ahead of the start sites of bidirectional replication, within the pre-replicative complex region; topoisomerase I is bound in M, early G1 and G1/S border and topoisomerase II in M and the middle of G1. The Orc2 protein competes for the same sites of the origin bound by either topoisomerase in different moments of the cell cycle; furthermore, it interacts on the DNA with topoisomerase II during the assembly of the pre-replicative complex and with DNA-bound topoisomerase I at the G1/S border. Inhibition of topoisomerase I activity abolishes origin firing. Thus, the two topoisomerases are closely associated with the replicative complexes, and DNA topology plays an essential functional role in origin activation.